Peran Drama Konflik sebagai Strategi Komunikasi Pemasaran pada Akun Elvara - Finna Maulana Kismawardani; Masnia Ningsih; Fatihatul Lailiyah (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
In marketing communication, there are several important aspects that need to be a priority for a businessman, one of which is promotion. Promotion is a strategy carried out by a company to attract and make consumers aware of the products offered. Along with technological advances, business people are now increasingly utilizing e-commerce platforms, such as Tiktokshop, to promote and advertise their products. Tiktokshop also has a live streaming feature whose purpose is to introduce business people's products in detail to consumers directly. Now, one of the Tiktok accounts that uses promotions via live streaming is the Elvara account. Elvara is one of the Tiktok accounts that sells skincare products using a unique marketing communication strategy. Presenting household conflict dramas every day when offering products on live streaming. The purpose of the study was to determine the role of conflict drama as a marketing communication strategy in promoting skincare products offered during live streaming. This study uses a qualitative approach method with the 7P marketing mix theory which includes product, price, place, promotion, people, process, and physical evidence. The results of this study indicate that promotion through conflict drama can influence decision making by loyal consumers (customers) to repeat orders and potential consumers to directly purchase skincare products offered by the Elvara account.